Identification of a Suitable Solid Carrier as a Matrix for the Permeable Reactive Barrier of Laboratory Scale Model Aquifer for Atrazine Degradation - Shrestha, Binita K; Shakya, Pawan Raj; Soares, MIM (Tribhuvan University Journal, 2010)
Three different types of physical substrata such as sand, granualar activated carbon (GAC) and plastic macaroni beads were selected to identify a suitable solid carrier as a course matrix for the permeable reactive barrier (PRB) in a sand filled two-dimensional laboratory-scale model aquifer. An adhesion experiment was performed and tested with Pseudomonas sp ADP (PASP) under agitated as well as static conditions. In static conditions, adhesion to GAC was the highest (80%) followed by that to beads (60%). No adhesion to sand was observed under static or agitated conditions. Since atrazine is adsorbed by GAC, its bioavailability for degradation by PADP may be affected. To test this, simultaneous loss of atrazine and release of chloride (dechlorination, the first step in the pathway of atrazine degradation by PADP) were determined in the presence and absence of GAC. Although cells remained viable, no significant chloride release was detected. Thus, plastic macaroni beads were identified and selected as the most suitable support for PADP in the biological permeable reactive barrier (BPRB) of the model aquifer. Key words: Suitable Solid; Laboratory Scale; PADP Tribhuvan University Journal Vol. XXV, No. 1, 2005 Page:119-128 Uploaded date: 26, September, 2010